Infants’ Learning of Phonological Status - Seidl, Amanda; Cristia, Alejandrina (Frontiers in Psychology, 2012)
There is a substantial literature describing how infants become more sensitive to differences between native phonemes (sounds that are both present and meaningful in the input) and less sensitive to differences between non-native phonemes (sounds that are neither present nor meaningful in the input) over the course of development. Here, we review an emergent strand of literature that gives a more nuanced notion of the problem of sound category learning. This research documents infants’ discovery of phonological status, signaled by a decrease in sensitivity to sounds that map onto the same phonemic category vs. different phonemic categories. The former phones are present in the input, but their difference does not cue meaning distinctions because they are tied to one and the same phoneme. For example, the diphthong I in I’m should map to the same underlying category as the diphthong in I’d, despite the fact that the first vowel is nasal and the second oral. Because such pairs of sounds are processed differently than those than map onto different phonemes by adult speakers, the learner has to come to treat them differently as well. Interestingly, there is some evidence that infants’ sensitivity to dimensions that are allophonic in the ambient language declines as early as 11 months. We lay out behavioral research, corpora analyses, and computational work which sheds light on how infants achieve this feat at such a young age. Collectively, this work suggests that the computation of complementary distribution and the calculation of phonetic similarity operate in concert to guide infants towards a functional interpretation of sounds that are present in the input, yet not lexically contrastive. In addition to reviewing this literature, we discuss broader implications for other fundamental theoretical and empirical questions.